At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Get quick and reliable solutions to your questions from a community of seasoned experts on our user-friendly platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Sure! Let's tackle each part of the problem one by one.
### Part 8: Finding the quadratic polynomial
We are asked to find the quadratic polynomial whose sum of the zeroes is [tex]\(-5\)[/tex] and the product of the zeroes is [tex]\(6\)[/tex].
In general, for a quadratic polynomial [tex]\(ax^2 + bx + c\)[/tex]:
- The sum of the zeroes, [tex]\(\alpha + \beta\)[/tex], is given by [tex]\(-\frac{b}{a}\)[/tex]
- The product of the zeroes, [tex]\(\alpha \beta\)[/tex], is given by [tex]\(\frac{c}{a}\)[/tex]
Given:
- The sum of zeroes ([tex]\(\alpha + \beta\)[/tex]) = [tex]\(-5\)[/tex]
- The product of zeroes ([tex]\(\alpha \beta\)[/tex]) = [tex]\(6\)[/tex]
For a standard quadratic polynomial in the form [tex]\(x^2 + bx + c\)[/tex], we can directly match the coefficients:
- The sum of the zeroes introduces the term [tex]\(\sum{x}\)[/tex] to be [tex]\(-b\)[/tex], thus [tex]\(b = - (\text{sum of zeroes}) = -(-5) = 5\)[/tex].
- The product of the zeroes gives the constant term [tex]\(c\)[/tex], thus [tex]\(c = \text{product of zeroes} = 6\)[/tex].
Thus, the quadratic polynomial is:
[tex]\[ x^2 + 5x + 6 \][/tex]
### Part 9: Finding the value of [tex]\(m\)[/tex]
Now, we are given the polynomial [tex]\( p(x) = 4x^2 - 6x - m \)[/tex] and we need to find the value of [tex]\(m\)[/tex] such that this polynomial is exactly divisible by [tex]\(x - 3\)[/tex].
For a polynomial to be exactly divisible by another polynomial [tex]\(x - a\)[/tex], the remainder when the polynomial is divided by [tex]\(x - a\)[/tex] must be zero. This means that [tex]\(p(a) = 0\)[/tex].
Given that [tex]\(x - 3\)[/tex] is a factor of [tex]\(p(x)\)[/tex], we have:
[tex]\[ p(3) = 0 \][/tex]
Let's substitute [tex]\(x = 3\)[/tex] into the polynomial [tex]\( p(x) \)[/tex]:
[tex]\[ p(3) = 4(3)^2 - 6(3) - m \][/tex]
Calculating the terms inside:
[tex]\[ 4(3)^2 = 4 \cdot 9 = 36 \][/tex]
[tex]\[ -6(3) = -18 \][/tex]
So,
[tex]\[ p(3) = 36 - 18 - m = 0 \][/tex]
Simplifying this equation to solve for [tex]\(m\)[/tex]:
[tex]\[ 36 - 18 - m = 0 \][/tex]
[tex]\[ 18 - m = 0 \][/tex]
[tex]\[ m = 18 \][/tex]
Thus, the value of [tex]\(m\)[/tex] is:
[tex]\[ m = 18 \][/tex]
### Summary:
1. The quadratic polynomial whose sum of zeroes is [tex]\(-5\)[/tex] and product is [tex]\(6\)[/tex] is [tex]\(x^2 + 5x + 6\)[/tex].
2. The value of [tex]\(m\)[/tex] that makes the polynomial [tex]\(p(x) = 4x^2 - 6x - m\)[/tex] exactly divisible by [tex]\(x - 3\)[/tex] is [tex]\(18\)[/tex].
### Part 8: Finding the quadratic polynomial
We are asked to find the quadratic polynomial whose sum of the zeroes is [tex]\(-5\)[/tex] and the product of the zeroes is [tex]\(6\)[/tex].
In general, for a quadratic polynomial [tex]\(ax^2 + bx + c\)[/tex]:
- The sum of the zeroes, [tex]\(\alpha + \beta\)[/tex], is given by [tex]\(-\frac{b}{a}\)[/tex]
- The product of the zeroes, [tex]\(\alpha \beta\)[/tex], is given by [tex]\(\frac{c}{a}\)[/tex]
Given:
- The sum of zeroes ([tex]\(\alpha + \beta\)[/tex]) = [tex]\(-5\)[/tex]
- The product of zeroes ([tex]\(\alpha \beta\)[/tex]) = [tex]\(6\)[/tex]
For a standard quadratic polynomial in the form [tex]\(x^2 + bx + c\)[/tex], we can directly match the coefficients:
- The sum of the zeroes introduces the term [tex]\(\sum{x}\)[/tex] to be [tex]\(-b\)[/tex], thus [tex]\(b = - (\text{sum of zeroes}) = -(-5) = 5\)[/tex].
- The product of the zeroes gives the constant term [tex]\(c\)[/tex], thus [tex]\(c = \text{product of zeroes} = 6\)[/tex].
Thus, the quadratic polynomial is:
[tex]\[ x^2 + 5x + 6 \][/tex]
### Part 9: Finding the value of [tex]\(m\)[/tex]
Now, we are given the polynomial [tex]\( p(x) = 4x^2 - 6x - m \)[/tex] and we need to find the value of [tex]\(m\)[/tex] such that this polynomial is exactly divisible by [tex]\(x - 3\)[/tex].
For a polynomial to be exactly divisible by another polynomial [tex]\(x - a\)[/tex], the remainder when the polynomial is divided by [tex]\(x - a\)[/tex] must be zero. This means that [tex]\(p(a) = 0\)[/tex].
Given that [tex]\(x - 3\)[/tex] is a factor of [tex]\(p(x)\)[/tex], we have:
[tex]\[ p(3) = 0 \][/tex]
Let's substitute [tex]\(x = 3\)[/tex] into the polynomial [tex]\( p(x) \)[/tex]:
[tex]\[ p(3) = 4(3)^2 - 6(3) - m \][/tex]
Calculating the terms inside:
[tex]\[ 4(3)^2 = 4 \cdot 9 = 36 \][/tex]
[tex]\[ -6(3) = -18 \][/tex]
So,
[tex]\[ p(3) = 36 - 18 - m = 0 \][/tex]
Simplifying this equation to solve for [tex]\(m\)[/tex]:
[tex]\[ 36 - 18 - m = 0 \][/tex]
[tex]\[ 18 - m = 0 \][/tex]
[tex]\[ m = 18 \][/tex]
Thus, the value of [tex]\(m\)[/tex] is:
[tex]\[ m = 18 \][/tex]
### Summary:
1. The quadratic polynomial whose sum of zeroes is [tex]\(-5\)[/tex] and product is [tex]\(6\)[/tex] is [tex]\(x^2 + 5x + 6\)[/tex].
2. The value of [tex]\(m\)[/tex] that makes the polynomial [tex]\(p(x) = 4x^2 - 6x - m\)[/tex] exactly divisible by [tex]\(x - 3\)[/tex] is [tex]\(18\)[/tex].
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.